Psychometric properties of the childhood depression scale in primary school students of a national educational institution in Lima, 2017 - Manrique Tapia, César Raúl (2017)
This research, of a technological type and psychometric character, has as a general purpose to build and determine the psychometric properties of the Child Depression Scale-CDS in children aged from 6 to 11, from the district of Comas, in Lima. The sample of 100 children was obtained by non-probabilistic sampling by judgment. Content validity was developed by judgment of 5 experts and V. Aiken index p>0.80 in 36 items, V. Lawshe p>0.60 in 35 items and Binomial test p<0.05 in 36 items were obtained. The item-test and item-scale fixed correlations were also analyzed where 17 and 8 items were removed respectively. Construct validity was obtained by the exploratory factor analysis that showed 4 factors explaining 52.7 % of the variability. The internal consistency reliability through Cronbach Alpha obtained in the general scale was 0.372. General percentiles, as well as cutoffs and the low, medium, and high descriptive levels in the overall scale and its indicators were constructed. Finally, a descriptive study in the sample of the 100 children was made; it showed a medium level of presence of the child depression, in children aged from 6 to 11.